The Secondary Data Analysis on the Impact of Corporate Social Responsibility (CSR) towards the Competitiveness of Sharia Corporations in the International Market - Yusup, Akhmad; Popon Srisusilawati; Cecep Soleh Kurniawan (Universitas Islam Negeri Alauddin Makassar, 2024)
In an era where corporate ethics are increasingly scrutinized, the question arises: can social responsibility truly enhance a company's competitive edge? This study aims to analyze the impact of Corporate Social Responsibility (CSR) on the competitiveness of Sharia companies in the international market. Using a quantitative approach and secondary data from 30 Sharia companies listed on the stock exchange during the period of 2015-2023, this research found a significant positive relationship between CSR and the competitiveness of companies. The regression analysis results indicate that each one-unit increase in CSR value is associated with a 0.45 unit increase in company competitiveness. These findings suggest that Sharia companies actively engaged in CSR not only enhance their reputation but also strengthen their position in the international market. This research contributes significantly to the understanding of the role of CSR in the business strategies of Sharia companies.